Multidisciplinary design and optimisation of conceptual rotorcraft powerplants for operational performance and environmental impact. (July 2015) - Ali, F.; Tzanidakis, K.; Goulos, I.; Pachidis, V.; d'Ippolito, R.
Abstract: This paper demonstrates the application of an integrated rotorcraft multidisciplinary design and optimisation framework, deployed for the purpose of preliminary design and assessment of optimum regenerative powerplant configurations for rotorcraft applications. The proposed approach comprises a wide-range of individual modelling theories applicable to rotorcraft flight dynamics, gas turbine engine performance and weight estimation as well as a physics-based stirred reactor model, for the rapid estimation of various gas turbine gaseous emissions. A single-objective Particle Swarm Optimiser is coupled with the aforementioned rotorcraft design framework. The overall methodology is deployed for the design and optimisation of a reference multipurpose Twin-Engine-Light civil rotorcraft, modelled after the Bo105 helicopter, which employs two Rolls-Royce Allison 250-C20B turboshaft engines. Through the implementation of a single-objective optimisation strategy, notionally based optimum engine design configurations are acquired in terms of engine weight, mission fuel burn and mission gaseous emissions inventory at constant technology level. The acquired optimum regenerative engine configurations are subsequently deployed for the design of conceptual rotorcraft regenerative engine configurations, targeting improved mission fuel economy, enhanced payload-range capability as well as overall environmental impact, while maintaining the respective rotorcraft airworthiness requirements. The proposed methodology essentially constitutes as an enabler for designing rotorcraft powerplants within realistic, three-dimensional operations and towards realising their associated design trade-offs at mission level.